Pengaruh Kualitas Produk, Customer Experience dan Citra Merek Terhadap Kepuasan Konsumen pada Produk Cimory Yogurt - Diya Ayu Rahmawati; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how much influence product quality, customer experience and brand image have on consumer satisfaction with Cimory yogurt products. The population used in this research were UPN Veteran Jawa Timur students who had purchased or consumed Cimory yogurt products. The sample in this study was 100 respondents, namely consumers of Cimory yogurt products for UPN Veteran Jawa Timur students. The sampling technique used in this research is a non-probability sampling technique with a purposive sampling approach. The type of research used in this research is associative research with a quantitative approach. Hypothesis testing used in this research includes Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, t Test, f Test and Coefficient of Determination Test. The results of this research show that product quality, customer experience and brand image simultaneously have a positive and significant effect on consumer satisfaction by obtaining a fcount of 96.221. Meanwhile, partially, product quality has a positive and significant effect on consumer satisfaction by obtaining a t-count of 2.704, customer experience has a positive and significant effect on consumer satisfaction by obtaining a t-count of 8.385 and brand image has a positive and significant effect on consumer satisfaction for Cimory yogurt products among students. UPN Veteran Jawa Timur obtained a t-count of 2.066.